Comorbidity of arterial hypertension and periodontitis: dental hypertension - Dmitry I. Trukhan; Anatoly F. Sulimov; Larisa Yu. Trukhan (LLC "MEDIAFORMAT", 2023)
Arterial hypertension and periodontitis are among the most common chronic diseases in the world. Poor periodontal health associated with an increased prevalence of hypertension may affect blood pressure control. Epidemiological data point to a potential association of periodontitis with elevated blood pressure levels and the prevalence of arterial hypertension. However, in the recommendations of Russian and European cardiologists, this connection is not considered. At the same time, in the last few years, possible mechanisms of the relationship between arterial hypertension and periodontal pathology have been actively discussed, and the results of large-scale studies, reviews and meta-analysis have been published. The review is devoted to the analysis of data on the relationship between arterial hypertension and periodontitis using the PubMed and Scopus electronic information databases. Possible mechanisms of this relationship include common risk factors, low-grade systemic inflammation, immune responses, periodontal bacteria, and endothelial dysfunction. The latest clinical studies and reviews confirming the relationship between arterial hypertension and periodontitis are considered. A positive effect of periodontal treatment on blood pressure control has been noted. The data available today indicate a close relationship between periodontitis and arterial hypertension, which necessitates the clarification of possible dental complaints and examination of the oral cavity during the collection of a patient's history of possible dental complaints and examination of the oral cavity during the supervision of patients with arterial hypertension by internists, and if they are present, referral of patients for consultation and treatment to a dentist . On the other hand, in order to increase the effectiveness of the treatment of periodontal diseases, it is advisable for the dentist to clarify the existing somatic pathology by sending the patient for consultation and treatment to an internist.